By the binomial theorem,
![](https://latex.codecogs.com/png.latex?\bg_white (3-x)^n=\sum_{k-0}^{n}\binom{n}{k}3^{n-k}(-x)^k=\sum_{k-0}^{n}\binom{n}{k}3^{n-k}(-1)^kx^k)
.
The (-1)
k tells us that the signs of the terms alternate, so we only need to focus on the magnitude. The above formula tells us that the coefficient of
xk has magnitude
![](https://latex.codecogs.com/png.latex?\bg_white |T_k|=\binom{n}{k}3^{n-k}=\frac{n!}{k!(n-k)!}\cdot 3^{n-k})
.
Therefore, the absolute value of the coefficient of
x4 and
x5 are
![](https://latex.codecogs.com/png.latex?\bg_white |T_4|=\frac{n!}{4!(n-4)!}\cdot 3^{n-4})
and
![](https://latex.codecogs.com/png.latex?\bg_white |T_5|=\frac{n!}{5!(n-5)!}\cdot 3^{n-5})
.
Since we want these to be equal, we have